2011
DOI: 10.1007/s10751-011-0302-z
|View full text |Cite
|
Sign up to set email alerts
|

Tests of fundamental theories with heavy ions at low-energy regime

Abstract: The current status of theoretical investigations of spectroscopic properties and fundamental interactions in highly charged ions is reviewed. Laying special attention on tests of quantum electrodynamics at strong fields recent progress in calculations of energy levels, hyperfine splitting and g factor values is reported. The parity nonconservation effect on the laser-induced 2 3 S 1 − 2 1 S 0 transition in heavy He-like ions is studied, which could serve as test scenario for the Standard Model in low-energy at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 87 publications
(80 reference statements)
0
12
0
Order By: Relevance
“…Therefore, in the Furry picture the electron-nucleus interaction is taken into account to all orders in αZ from the very beginning. The interaction with the quantized electromagnetic field and the interelectronic interaction are considered by the perturbation theory in the parameters α and 1/Z, respectively [58,[60][61][62][63][64]. We note that for very heavy ions the parameters α and 1/Z become comparable in magnitude, therefore, all the contributions can be classified by the powers of α.…”
Section: A Qed Formalismmentioning
confidence: 99%
“…Therefore, in the Furry picture the electron-nucleus interaction is taken into account to all orders in αZ from the very beginning. The interaction with the quantized electromagnetic field and the interelectronic interaction are considered by the perturbation theory in the parameters α and 1/Z, respectively [58,[60][61][62][63][64]. We note that for very heavy ions the parameters α and 1/Z become comparable in magnitude, therefore, all the contributions can be classified by the powers of α.…”
Section: A Qed Formalismmentioning
confidence: 99%
“…In many cases the precision of these calculations has reached a level that requires evaluations of quantum electrodynamics (QED) effects. To date, the rigorous calculations of the QED effects in middle-and high-Z systems are fully restricted to the 1/Z perturbation theory (see, e.g., [15][16][17][18][19] and references therein). The perturbation theory methods have been also extended to many-electron ions and atoms employing an effective screening potential instead of the Coulomb one [20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…1,2,8 Recent studies have shown that metal biocorrosion is caused even by enzymes peroxidases and catalases, produced by microorganisms exposed to oxygen. 6 According to some studies, the protection of metallic materials against the action of corrosive agents can be made by chemical substances as surfactants, for example, alkylpolyglucoside (APG), that can inhibit the corrosion of 907 carbon steel, and didodecylbenzyltriethylammonium chloride that have a good effect against corrosion of the carbon steel (apud 3 ).…”
Section: Anticorrosion Effect Of the Rhamnolipids Congenersmentioning
confidence: 99%
“…2,4,5 Studies have proven that the corrosion process occurs by the action of peroxidases and catalases, which are common enzymes produced by microorganisms exposed to oxygen. 6 Cases of crude oil leakage due to internal pipeline corrosion, generally caused by microbial action, are well reported worldwide. In addition to metal corrosion in pipelines and storage tanks, microbial action in the oil reservoir leads to fuel contamination, turbidity changes, and acidification of petroleum products.…”
Section: Introductionmentioning
confidence: 99%